IMPLEMENTASI ISAK 35 DALAM PENGELOLAAN KEUANGAN SYARIAH PONDOK PESANTREN AL-MUSTAQIM PAREPARE - Afifah, Rizki (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2025)
Good financial management is essential for the sustainability of Islamic boarding schools. Al-Mustaqim Islamic Boarding School in Parepare manages funds from the government and donors, but financial records are still manual and not fully compliant with sharia accounting standards. This study aims to analyze the implementation of ISAK 35 in sharia financial management and to examine the benefits of implementing ISAK 35 in financial reporting. This study uses a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews with the boarding school's principal, treasurer, and secretary, as well as through observation and documentation of financial reports. Data analysis techniques were carried out through data reduction, data presentation, and verification of conclusions to obtain a comprehensive picture of the implemented financial management system.The results of the study indicate that the Al-Mustaqim Islamic Boarding School in Parepare has not implemented ISAK 35 in the preparation of financial reports, so that the recording is still simple and not in accordance with sharia accounting standards. Then the main obstacles in the financial management of Islamic boarding schools include lack of funds, limited human resources, lack of socialization regarding accounting standards for non-profit organizations, and operational funding constraints. The novelty in this study lies in the focus of the implementation of ISAK 35 in the management of sharia finances at the Al-Mustaqim Islamic Boarding School in Parepare by providing suggestions, namely the importance of socialization of ISAK 35 to improve the quality of financial reports of non-profit organizations. The contribution of this study is to provide recommendations for improving the financial recording system and the implementation of ISAK 35, which can increase the efficiency, transparency, and accountability of Islamic boarding school financial management and support the sustainability of its operations.